PELATIHAN REPORTASE BERITA DALAM MENINGKATKAN KOMUNIKASI LISAN BAGI SISWA SMKN 2 GARUT - Melvina, Yayang Dwi; Nurhadi, Zikri Fachrul (Universitas Padjadjaran, 2024)
The background of the problem in this community service is the lack of understanding of reporting techniques so that oral communication skills among students are inadequate, especially in the Television Program Production and Broadcasting (PSPT) department of SMKN 2 Garut. This is caused by the limited teaching materials and direct training in journalism. By having an understanding of reporting techniques, students will have oral communication skills, students will have a level of confidence to speak in front of the camera, because oral communication skills are very important to have in the world of work and education. This applies to the students studying PSPT in SMKN 2 Garut, where they must understand reporting techniques and have good oral communication skills when viewed from the department they are currently studying. Therefore, this community service activity needs to be carried out to provide knowledge about reporting techniques and improve oral communication skills for students of SMKN 2 Garut. The purpose of this service is to describe the results of community service activities in the form of news reporting training for students in improving oral communication, so that they can appear confident in front of the camera and even the general public. The method used in this community service is a 3-day training with the technique of providing material, discussion and direct practice in the field. The result of this community service activity is that students are able to understand how the reporting training is carried out so that they can improve their oral communication and build their confidence by producing journalistic works in the form of video reports. It can be concluded that this news reporting training is said to be successful from the previous 58.7% to 91.7% who know about news reporting and increased student oral communication after participating in this training.Latar belakang permasalahan pada pengabdian ini adalah kurangnya pemahaman mengenai teknik reportase, sehingga kemampuan komunikasi lisan di kalangan para pelajar kurang lancar, terutama pada jurusan Produksi dan Siaran Program Televisi (PSPT) SMKN 2 Garut. Hal tersebut disebabkan oleh keterbatasannya bahan ajar dan pelatihan langsung dalam bidang jurnalistik. Dengan memiliki pemahaman mengenai teknik reportase, para siswa/i akan memiliki kemampuan komunikasi secara lisan dan memiliki tingkat rasa percaya diri untuk berbicara di depan kamera, karena kemampuan komunikasi lisan merupakan hal yang sangat penting untuk dimiliki di dalam dunia pekerjaan maupun pendidikan. Seperti pada para pelajar jurusan PSPT SMKN 2 Garut, di mana mereka harus memahami teknik reportase dan memiliki kemampuan komunikasi lisan yang baik jika dilihat dari jurusan apa yang sedang mereka tekuni. Oleh karena itu, kegiatan pengabdian ini perlu dilakukan untuk memberikan pengetahuan seputar teknik reportase dan meningkatkan keterampilan komunikasi lisan bagi siswa/i SMKN 2 Garut. Tujuan pengabdian ini, untuk mendeskripsikan hasil kegiatan pengabdian kepada masyarakat berupa pelatihan reportase berita bagi siswa/i dalam meningkatkan komunikasi lisan, sehingga mereka bisa tampil percaya diri di hadapan kamera, bahkan khalayak umum. Metode yang digunakan dalam pengabdian ini yaitu pelatihan selama 3 hari dengan teknik pemberian materi, diskusi, dan praktik langsung ke lapangan. Hasil dari kegiatan pengabdian ini adalah para siswa/i mampu memahami bagaimana pelatihan reportase yang dilakukan sehingga mampu meningkatkan komunikasi lisan mereka dan menimbulkan rasa percaya diri dengan menghasilkan karya jurnalistik berupa video reportase. Dapat disimpulkan bahwa, pelatihan reportase berita ini dikatakan berhasil dari yang sebelumnya 58,7% menjadi 91,7% yang mengetahui tentang reportase berita dan meningkatnya komunikasi lisan siswa/i setelah mengikuti pelatihan ini.